Application of the Cylindrical Wave Approach to the Simulation of Buried Utilities - Fabrizio Frezza; Lara Pajewski; Cristina Ponti; Giuseppe Schettini (International Journal of Geophysics)
The cylindrical wave approach is resumed. It is a full-wave technique for the solution of the two-dimensional plane-wave scattering problem by a set of perfectly conducting and dielectric cylinders buried in a dielectric half-space, or in a finite-thickness slab. This method can be applied for simulating scenarios with cylindrical inhomogeneities buried in the earth. New numerical results are presented, concerning the simulation of buried utilities. In particular, metallic pipes and air cavities are simulated.